A study of e-services of bank with special reference to private banks, Ahmednagar - Nimbalkar, Atul Arun; Deodhar, Nachiket (International research journal of management, IT and social sciences, 2015)
E-banking means electronic banking which is popularly known as anywhere banking. Electronic banking also known as EFT (Electronic Fund Transfer) means transfer amount online from one account to another account rather by using a physical cheque. Information technology has taken an important place in the future development of financial service, especially the banking sector transaction are affected more than any other financial provider groups. Increased use of mobile services and the use of the internet as a new distribution channel for banking transactions and international trading requires more attention to e-banking security against fraudulent activities. The development and the increasing progress that is being experienced in the Information and Communication Technology have brought about a lot of changes in almost all facets of life. In the Banking Industry, it has been in the form of online banking, which is now replacing the traditional banking practice. Although it is proving boon to all sectors especially to all types of customers and financial sector but its growing use without awareness has also attracted many crimes and frauds.